Pengaruh Media Puzzle Terhadap Motivasi Belajar Materi Penjumlahan Matematika Siswa Kelas II SDN 26 Sei Bun - Ya’Julyanto; Donata Yona (Lembaga Teewan Journal Solutions, 2026)
This study aims to determine the effect of using puzzle media on students’ learning motivation. The research subjects consisted of 29 students. The approach used was quantitative with a One Group Pre-Test Post-Test design. The data collection Instruments were a learning motivation questionnaire and documentation. The results showed an effect on students’learning motivation after the treatment. This is evident from the average pre-test score of 39,48 and the post-test 72,62 with an increase of 33,14 after the use of puzzle media, and a significance value of 0,000. Based on the SPSS 26 output in the Test Statistics table, HO was rejected and Ha was accepted. This indicates a difference in the average scores of the pre-test and post-test, proving the effect of using puzzle media on learning motivation in addition material of mathematics for second grade students at SDN 26 Sei Bun.